Sistem Informasi Pengelolaan Asrama Putra Universitas Katolik Santo Thomas Berbasis Web Dengan Metode Waterfall - Sephia Sari Peranginangin; Andy Paul Harianja (Program Studi Informatika Universitas PGRI Yogyakarta, 2026)
This study examines the management system of the Santo Thomas Catholic University Men's Dormitory, which is still manual and conventional. This conventional method often causes problems, such as the risk of data errors, loss of archives, and administrative inefficiency. The main objective of this study is to design and implement a web-based dormitory management information system by applying the Waterfall Method. This development method was chosen because of its structured and systematic nature, from needs analysis to testing. The results of the implementation show that the resulting system is capable of automating the registration process, room management, payment recording, and report generation. System testing proves that this system runs according to user needs and significantly improves the speed and accuracy of dormitory management administration. These findings have important implications for the transformation of campus facility management to be more structured, efficient, and accessible.